(untitled) (Texas Journal of Medical Science, 2024)
The article is devoted to the problems of using metabolic drugs that affect intracellular energy exchange processes. These drugs, which are proposed to be called energotropic, are becoming increasingly popular in modern medicine. The more urgent the task of determining the area of pathogenetic justification for their purpose becomes. The authors propose for discussion a range of indications for energotropic therapy. Various examples of the successful use of energotropic drugs in pediatrics are discussed